Cilostazol treatment for preventing adverse cardiovascular events in patients with type 2 diabetes and coronary atherosclerosis: Long‐term follow‐up of the ESCAPE study. Issue 8 (5th August 2022) - Sohn, Minji; Chun, Eun Ju; Lim, Soo
Abstract: Background: Previously, in the ESCAPE study, a randomized controlled trial, we found that 12 months of cilostazol administration significantly decreased coronary artery stenosis and the noncalcified plaque component compared with aspirin. The goal of the current study was to evaluate the effect of cilostazol treatment on cardiovascular events up to 7 years after the end of the original study. Methods: After the end of the ESCAPE study with patients with type 2 diabetes mellitus (T2DM) and mild to moderate coronary artery stenosis, we decided to extend the ESCAPE study to investigate the long‐term effect of cilostazol and aspirin, named the ESCAPE‐extension study. The study participants had been investigated for cardiovascular events for up to 7 years, bringing the total follow‐up time to a median of 5.2 years (interquartile range 3.6‐6.7 years). Adverse events were also investigated. Results: Among 100 participants from the original study, 88 were included in this extension study. Cilostazol treatment reduced the incidence of cardiovascular events in the patients with T2DM when compared with aspirin for a 5.2‐year median follow‐up (hazard ratio 0.24; 95% CI, 0.07‐0.83). The cardiovascular benefit of cilostazol therapy was maintained along with age, sex, systolic blood pressure, low‐density lipoprotein cholesterol, and coronary artery calcium score. No serious adverse events in the cilostazol group were noted in the follow‐up period. Conclusions: In this ESCAPE‐extension study, cilostazol treatment proved its efficacy in reducing cardiovascular events compared with aspirin in diabetic patients with subclinical coronary artery disease, suggesting the beneficial role of cilostazol in the primary prevention of cardiovascular disease. Abstract : Highlights In this ESCAPE‐extension study, cilostazol treatment reduced the incidence of adverse cardiovascular events in patients with type 2 diabetes when compared with aspirin for a 5.2‐year median follow‐up. During the follow‐up period, no adverse events were noted in the cilostazol group that exceeded those in the aspirin group. Cilostazol may be an effective antiplatelet therapy to lower cardiovascular risk in patients with type 2 diabetes who have well‐controlled low‐density lipoprotein‐cholesterol levels with statin treatment. A longer‐term study with a larger sample size is required to confirm this premise. 摘要: 背景: ESCAPE研究是一项随机对照试验, 在该研究中我们发现与阿司匹林相比, 西洛他唑给药12个月可显著降低冠状动脉狭窄和非钙化斑块成分。本研究旨在评估在原始研究结束7年后西洛他唑治疗对心血管事件的影响。 方法: 2型糖尿病合并轻中度冠状动脉狭窄患者的ESCAPE研究结束后, 我们决定延长ESCAPE研究, 以观察西洛他唑和阿司匹林的长期疗效, 命名为ESCAPE‐扩展研究。研究参与者被追踪心血管事件长达7年, 总的随访时间中位数为5.2年(四分位差范围为3.6‐6.7年)。对不良事件也进行了调查。 结果: 在原始研究的100名参与者中, 有88人被纳入本次扩展研究。在5.2年的中位随访中, 与阿司匹林相比, 西洛他唑治疗可降低T2DM患者的心血管事件发生率(风险比[HR] = 0.24;95%置信区间[CI] 0.07‐0.83)。西洛他唑治疗的心血管获益与年龄、性别、收缩压、低密度脂蛋白胆固醇和冠状动脉钙评分保持一致。随访期间, 西洛他唑组未发现严重不良事件。 结论: 在本次ESCAPE‐扩展研究中, 西洛他唑治疗糖尿病合并亚临床冠状动脉疾病患者的心血管事件较阿司匹林明显减少, 提示西洛他唑在心血管疾病一级预防中具有有益作用。